2017
DOI: 10.3389/fpls.2017.01545
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly of the Camellia nitidissima Transcriptome Reveals Key Genes of Flower Pigment Biosynthesis

Abstract: The golden camellia, Camellia nitidissima Chi., is a well-known ornamental plant that is known as “the queen of camellias” because of its golden yellow flowers. The principal pigments in the flowers are carotenoids and flavonol glycosides. Understanding the biosynthesis of the golden color and its regulation is important in camellia breeding. To obtain a comprehensive understanding of flower development in C. nitidissima, a number of cDNA libraries were independently constructed during flower development. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…Their deduction has already been verified using heterologous expression of the FLS genes in tobacco, in which transgenes inhibiting the expression of DFR promoted flavonol accumulation, resulting in white flowers. Many similar results have confirmed that DFR and FLS gene products compete for common substrates in the biosynthetic pathways of anthocyanins and flavonols, respectively, thereby determining red or white color formation of flowers [14,38,39].…”
Section: Key Genes In the Anthocyanin Pathway Affect Coloration In Whmentioning
confidence: 68%
See 2 more Smart Citations
“…Their deduction has already been verified using heterologous expression of the FLS genes in tobacco, in which transgenes inhibiting the expression of DFR promoted flavonol accumulation, resulting in white flowers. Many similar results have confirmed that DFR and FLS gene products compete for common substrates in the biosynthetic pathways of anthocyanins and flavonols, respectively, thereby determining red or white color formation of flowers [14,38,39].…”
Section: Key Genes In the Anthocyanin Pathway Affect Coloration In Whmentioning
confidence: 68%
“…Li et al [15] have verified that the taxonomic relationships of wild camellias can be identified using 25 delphinidin and cyanidin anthocyanins from different wild camellia flowers. In the development of golden flower tea (Camellia nitidissima), anthocyanins were not detected [14].…”
Section: Effect Of Content and Types Of Anthocyanins On Coloration Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the transcriptomes of tea plant collected from different developmental stages or under different stresses or response to different hormones, we also literately gathered a total of nine transcriptomes from its close relatives, including C. azalea (Fan et al ., ), C. japonica (Li et al ., ), C. meiocarpa (Feng et al ., ), C. nitidissima (Zhou et al ., ), C. oleifera (Xia et al ., ), C. reticulate (Yao et al ., ), C. sasanqua (Huang et al ., ), C. chekiangoleosa (Wang et al ., ) and C. taliensis (Zhang et al ., ). The detail information of each transcriptome that comprises published journal, authors, study background, main conclusion, data accession numbers and investigated tissues was collected.…”
Section: Data Contentmentioning
confidence: 99%
“…Similar WGCNA analysis was used in golden camellia to identify unigenes correlated with flower color, and CHS, F3H, ANS and FLS were found to play critical roles in regulating the formation of flavonols and anthocyanidins [29].…”
Section: Comparison Of the Genes Related To The Biosynthesis Of Flavomentioning
confidence: 99%